2017
DOI: 10.1109/jbhi.2016.2597145
|View full text |Cite
|
Sign up to set email alerts
|

An Open Benchmark Challenge for Motion Correction of Myocardial Perfusion MRI

Abstract: Cardiac magnetic resonance perfusion examinations enable non-invasive quantification of myocardial blood flow. However, motion between frames due to breathing must be corrected for quantitative analysis. Although several methods have been proposed, there is a lack of widely available benchmarks to compare different algorithms. We sought to compare many algorithms from several groups in an open benchmark challenge. Nine clinical studies from two different centers comprising normal and diseased myocardium at bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
0
30
0
1
Order By: Relevance
“…In fact, several MRI studies reported an underestimation of MBF . In those studies, the MBF values were analyzed with regard to issues of quantification algorithms, applied MRI signal intensity corrections, interstudy repeatability, or motion correction .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, several MRI studies reported an underestimation of MBF . In those studies, the MBF values were analyzed with regard to issues of quantification algorithms, applied MRI signal intensity corrections, interstudy repeatability, or motion correction .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several MRI studies reported an underestimation of MBF . In those studies, the MBF values were analyzed with regard to issues of quantification algorithms, applied MRI signal intensity corrections, interstudy repeatability, or motion correction . For hyperemia, MBF underestimation was more pronounced in comparison to microsphere perfusion measurements; however, it is well‐known that the microsphere technique somewhat overestimates MBF in regions of high flow, and underestimates MBF in regions of low flow .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Registration was used to compensate for the motion from the free‐breathing perfusion acquisitions. Rigid body registration in 2D has been shown to provide comparable perfusion values compared with nonrigid registration techniques . Although little study has been done in extending this concept to 3D, a 3D rigid‐body registration technique including through‐plane motion was found to provide reliable results for this work.…”
Section: Methodsmentioning
confidence: 95%